Bio-physical removal of heavy metal from aqueous solution - Kutty, S.R.M. (Taylor and Francis Inc., 2016)
The aim of this study was to compare the performance of a suspended growth bioreactor and a combined bio-physical bioreactor for Zn2+ removal from aqueous solution. Two identical bioreactors (8.5Â L each) were operated at a fixed HRT of 29.1Â h. The suspended growth bioreactor was used as the control reactor and contained only sludge. The bio-physical bioreactor contains sludge and a low-cost adsorbent derived from groundwater treatment plant sludge. The influent Zn2+ concentration was varied from 0.5 to 15Â mg/L in 8 experimental phases. Influent and effluent Zn2+ concentration was monitored daily. Phase 1 (day 1â15) and phase 2 (day 16â29) were used as acclimation period for both bioreactors, respectively. Results show that Zn2+ removal increased with increasing influent Zn2+ concentration from 0.5 to 1.0Â mg/L (phases 3â4) but fluctuated thereafter for the suspended growth bioreactor. Zn2+ removal in the bio-physical bioreactor increased with increasing influent Zn2+ concentration from 0.5 to 10Â mg/L (phases 3â7) and decreased with further increase in influent Zn2+ concentration to 15Â mg/L (phase 8). The effluent Zn2+ concentration in phase 8 for the suspended growth and the bio-physical bioreactors were 58.7 and 90, respectively. The higher removal of Zn2+ in the bio-physical bioreactor was due to heavy metal tolerance and the resistance in heavy metal toxicity on the microbial community of the combined system. Â© 2016 Balaban Desalination Publications. All rights reserved.